Pengaruh Pemanfaatan Artificial Intelligence (AI) Learning Tools Terhadap Motivasi Belajar Intrinsik Mahasiswa Universitas Pamulang - Dea Karolina; Dwi Yulianto; Muhammad Rosyid Rafiudin; Kartika Johar Ngafisah; Ria Aulia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study examines the effect of utilizing Artificial Intelligence (AI) Learning Tools on the intrinsic learning motivation of students at Universitas Pamulang. AI Learning Tools such as ChatGPT, Google Gemini, and Microsoft Copilot are increasingly used by students to support academic activities, yet their influence on intrinsic motivation remains underexplored, particularly within the Indonesian higher education context. This study employs a quantitative approach with a survey method, grounded in the Technology Acceptance Model (TAM) and Self-Determination Theory (SDT). Data were collected from 100 students of Universitas Pamulang across five faculties who actively use AI Learning Tools, selected through purposive sampling, and analyzed using simple linear regression with IBM SPSS. The results indicate that the utilization of AI Learning Tools has a positive and significant effect on students' intrinsic learning motivation (B = 0.150; t = 5.372; p = 0.000), with the regression equation Y = 8.285 + 0.150X and a coefficient of determination (R²) of 0.227, meaning AI Learning Tools utilization explains 22.7% of the variance in intrinsic learning motivation, while the remaining 77.3% is influenced by other factors outside the model. These findings confirm the relevance of TAM and SDT in explaining how perceived ease of use and usefulness of AI technology can foster students' autonomous, competence-driven learning motivation.